Effects of thermal annealing on the properties of highly reflective Nc-Si: H/A-Cnx: H multilayer films prepared by rf PECVD technique - Rashid, N.M.A.; Ritikos, R.; Goh, B.T.; Gani, S.M.A.; Muhamad, M.R.; Rahman, S.A. (2011)
The effects of thermal annealing in the range of 100-700Â°C on highly reflecting multilayer thin film consisting of 7 periods of alternating nc-Si:H/a-CNx:H layers prepared by radio-frequency plasma enhanced chemical vapour (r.f. PECVD) deposition technique were investigated. The films were deposited on quartz and <111> p-type c-Si substrate and were studied using ultra-violet-visible-near infrared (UV-VisNIR) and Fourier transform infrared (FTIR) spectroscopy. The as-deposited multilayered films show high reflectivity and wide stop band width at a wavelength of approximately 650 Â± 60 nm and the value starts to reduce as the annealing temperature, TA increase. Its FTIR spectra showed the formation of Si-H and Si-H2 bonds in the ncSi:H layer and C=C, C=N, Câ¡N, C-H and N-H bonds in a-CNx:H layer. The films remain thermally stable up to the TA of 400Â°C and then begin to degrade above this temperature. The results shows that both a-CNx:H and nc-Si:H were affected by heat treatment.